The impact of the German 'DEAL' on competition in the academic publishing market. (24th November 2021) - Haucap, Justus; Moshgbar, Nima; Schmal, W. Benedikt
Abstract: In 2019 and 2020, German research institutions and publishers Wiley and Springer Nature closed the so‐called DEAL agreements to facilitate open access publishing for researchers with German affiliation. These researchers do not have to pay for publishing their articles open access in Wiley and Springer Nature journals, as libraries cover these fees collectively. We use all publications in chemistry from 2016 to 2020 to estimate the impact of the DEAL on eligible scientists' journal choice applying a difference‐in‐differences framework. Even in the short treatment period, publication patterns have changed. Eligible researchers have increased their publications in DEAL journals at the cost of other journals. Two competition concerns emerge: Authors may prefer to publish in DEAL journals, thereby creating a competitive advantage in attracting good papers. Libraries may be left with fewer funds and incentives to subscribe to or to fund open access in non‐DEAL journals. As academic journals are two‐sided platforms, these effects may further spur concentration.